A description of the hydrography between Cape Town and Antarctica along the GoodHope Transect between 2004-2012 - Jacobs, Christopher Richard (Department of Oceanography, 2015)
The Antarctic Circumpolar Current (ACC) within the Southern Ocean (SO) is the primary driver for global interoceanic exchanges. These exchanges form the foundation for the Meridional Overturning Circulation (MOC), a deep density driven circulation, which extends throughout the global oceans. The fronts of the ACC, consisting of several branches, separate zones of distinct water masses, thus identifying the location of the fronts and understanding their dynamics is of global importance. The GoodHope programme, is a repeat annual transect between South Africa and Antarctica, monitoring the exchanges within the Southeast Atlantic sector of the Southern Ocean. This is achieved through high resolution Expendable Bathythermograph (XBT) sampling. In this study XBT data over an eight year period (2004 – 2012) were investigated and analysed. One aim is to illustrate the variability of the fronts associated with the ACC using in-situ data from 21 transects during this eight year period. The Sub-tropical Front (STF) and Northern branch of the Sub-Antarctic Front (SAF-N) are seen to be the most variable with frontal latitudinal shifts ranging from 2-4° and 1-2° respectively. One cause of this high variability is the interaction of mesoscale features, particularly in the form of eddies and Agulhas rings. The southernmost fronts of the ACC, namely the Southern Antarctic Circumpolar front(sACCf), consisting of a Northern and Southern branch of the sACCf (sACCf-N and sACCf-S) and Southern Boundary (SBdy), also display high variability due to seasonality brought on by ice melt. The central fronts of the ACC, the Middle and Southern branches of the SAF (M-SAF and S-SAF)and Northern, Middle and Southern branches of the Polar Front (PF-N, PF-M and PF-S) remain throughout the eight year observations fairly constant, with shifts observed to be less than 1° of latitude. Grouping the Good Hope transects into austral summer periods, illustrates the di-pentadal nature of the STF, whereby the shifts are in response to mesoscale interactions. Comparing the mean position of the fronts and their position observed during a single winter cruise in July 2012, an overall Northward shift was observed with most of the fronts with significant shifts occurring in the SAF-N and PF-N. This is due to the outcrop of different water masses occurring further South ward and Northward respectively.